2021
DOI: 10.1111/iju.14614
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with prostate cancer and bone metastasis from the Japanese Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index cohort study

Abstract: Abbreviations & Acronyms 1CTP = cross-linked telopeptide parts of type I collagen ADT = androgen deprivation therapy ALP = alkaline phosphatase ARTA = androgen receptor-targeted agent BAP = bone alkaline phosphatase BMA = bone-modifying agent BSI = Bone Scan Index CRP = C-reactive protein HSN = hot spot number

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…After each metastatic hot spot is determined, the BSI is calculated as the sum of all such fractions using software (EXINI bone in Europe and North America; BONENAVI in Japan) [ 39 ]. The BSI has shown clinical impact as a prognostic biomarker in patients with prostate cancer [ 40 , 41 ]. It was reported that the BSI more appropriately reflected treatment response than visual interpretation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…After each metastatic hot spot is determined, the BSI is calculated as the sum of all such fractions using software (EXINI bone in Europe and North America; BONENAVI in Japan) [ 39 ]. The BSI has shown clinical impact as a prognostic biomarker in patients with prostate cancer [ 40 , 41 ]. It was reported that the BSI more appropriately reflected treatment response than visual interpretation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although BSI provided a relatively objective estimation of metastatic burden of PCa, especially with the assistance of computer-aided diagnostic system, it was essentially an indirect indicator reflecting disease aggressiveness [33,34]. Further analysis were required to set up thresholds for risk stratification of prognosis [35]. Besides, the calculation of BSI did not consider the different effects among metastasis sites, since metastases to appendicular skeleton, such as ribs and limbs, had been reported to be significantly correlated with poorer response to androgen deprivation therapy and shorter survival time [30].…”
Section: Discussionmentioning
confidence: 99%
“…We previously performed a multicenter study (30 hospitals in Japan) to identify prognostic factors, including the bone scan index (BSI), in patients with mHSPC ( n = 148) and mCRPC ( n = 99), and the findings obtained revealed that BSI was one of the significant prognostic factors for 3‐year OS (PROSTAT‐BSI study, Figure 1). 13 Of note, each attending physician determined the diagnosis of CRPC and the course of treatment. The patients were enrolled from 2012 to 2015.…”
Section: Methodsmentioning
confidence: 99%